Polyketone powder for laser sintering
By preparing aliphatic polyketone materials with bimodal melting characteristics, the deformation problem caused by the difference in melting and recrystallization temperatures in 3D printing is solved, and high-strength, toughness and high temperature resistance are achieved. It is suitable for printing complex and large parts, and has good recycling.
Patent Information
- Application Number
- JP2023559758
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-01
- Filing Date
- 2022-05-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-05-16
AI Technical Summary
In the existing 3D printing technology, the temperature difference between the melting and recrystallization temperatures of the crystalline or semi-crystalline thermoplastic polymer materials used is insufficient, resulting in the printing object being easily deformed or warped, limiting the printing ability of large or complex components.
Aliphatic polyketone materials with bimodal or multimodal melting characteristics are used to control their particle size and morphology to ensure that the material can effectively avoid deformation during the 3D printing process. Specific catalysts and treatment methods are used to prepare suitable polyketone powders for selective laser sintering, rapid sintering and multi-jet fusion technologies.
High strength, toughness, high temperature resistance and in some cases transparent printing materials can avoid deformation during 3D printing, suitable for printing of complex and large parts, and the materials can be recycled.
Smart Images

Figure 0007627817000008 
Figure 0007627817000009 
Figure 0007627817000010
Abstract
Description
[Technical field]
[0001] The present disclosure relates to aliphatic polyketone polymer powders for additive manufacturing. [Background technology]
[0002] Aliphatic polyketones have become promising polymers due in part to their physical properties and chemical resistance as low-cost engineering plastics. Polyketones are copolymers of ethylene (and / or other olefins or alkenes) and carbon monoxide, typically produced by copolymerization in the presence of a palladium (or other) catalyst, as described in U.S. Pat. Nos. 5,993,333 and 5,363,621. Aliphatic polyketones are then typically separated from the other components present in the polymerization reactor. These other components may include unreacted alkenes, unreacted carbon monoxide, methanol (or other) reaction medium, and catalyst. The polyketone product that has been separated from the other components (e.g., by separation and drying) is referred to as "reactor flake." This reactor flake is typically heated and extruded to form pellets for commercial use, due to its fine particle size that makes it difficult to handle and ship.
[0003] Powder-based methods of additive manufacturing include: Selective laser sintering (SLS) is a 3D printing technique that uses a laser to fuse powdered material in successive layers (see, for example, U.S. Patent No. 5,333,933). Rapid sintering (HSS) and multi-jet fusion (MJF) 3D printing utilize multiple jets that similarly deposit successive layers of infrared absorbing (IR absorbing) ink onto a powdered material, which is then exposed to IR energy for selective melting. Electrophotographic 3D printing utilizes a rotating photoconductor that builds an object layer-by-layer from a base.
[0004] Selective laser sintering (SLS), multi-jet fusion (MJF), and high speed sintering (HSS) 3D printing methods use the same type of floating, unfixed powder bed. They generally have the same material requirements to be compatible with the printing process, since the additively built object experiences similar stresses, just with different heating mechanisms to obtain the molten phase. Typically, a free-body diagram of the 3D printed object can be used to determine the expected residual stresses in the printed object. This is necessary to successfully build the object. If the residual stresses are too high, the object will deform or bend beyond tolerances.
[0005] Residual stresses have typically been minimized for these powder-bed based 3D printers by using crystalline or semi-crystalline thermoplastic polymers with a sufficiently large window between their melting and recrystallization temperatures. Unfortunately, this has been limited to polymers (e.g., polyamides) that have been successfully used to print large or complex parts using SLS and MJF methods, thus limiting the use of these additive manufacturing methods. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] U.S. Pat. No. 4,835,250 [Patent Document 2] US Patent Application Publication No. 2008 / 0058494 [Patent Document 3] U.S. Pat. No. 5,597,589 Summary of the Invention [Problem to be solved by the invention]
[0007] It would therefore be desirable to provide a thermoplastic polymer that avoids one or more of the problems for producing additively manufactured articles by methods such as SLS, HSS, MJF, and others mentioned above. In particular, it would be desirable to provide a thermoplastic polymer that can provide articles with high strength, toughness, high temperature resistance, flame retardancy, and in some cases, optical clarity. [Means for solving the problem]
[0008] Applicants have discovered aliphatic polyketones that have particular powder morphology and thermal properties that enable layer-by-layer manufacturing of these materials by floating powder bed processes. Surprisingly, in one example, polyketone powders exhibit overlapping DSC melting peaks that exhibit a bimodal or multimodal (e.g., trimodal, quadruple, or more) morphology, with a recrystallization peak characterized within the DSC melting peaks.
[0009] The first aspect of the invention is a thermoplastic elastomer having a bimodal melting peak as determined by an initial differential scanning calorimetry (DSC) scan at 20° C. / min, as well as a D peak of up to 300 micrometers. 90 The present invention relates to a composition comprising semi-crystalline polyketone powders having a particle size and an average particle size of equivalent spherical diameter between 1 micrometer and 150 micrometer. Surprisingly, these powders can be printed by floating powder bed additive manufacturing techniques such as SLS, HSS and MJF, even though they exhibit overlapping melting and recrystallization peaks (i.e., the onset temperature of the melting peak during heating is lower than the onset temperature of the recrystallization peak during cooling). Similarly, these powders exhibit good additive manufacturing recyclability, even though their thermal properties change, such as the melting peak becoming unimodal. Bimodal peak here means that the peak exhibits two maxima and one minimum between the onset and end temperatures, which can be determined manually or by commercially available curve fitting software.
[0010] A second aspect of the invention is a composition comprising a semi-crystalline polyketone powder having melting and recrystallization peaks that do not overlap as determined by differential scanning calorimetry (DSC) scanned at heating and cooling rates of 20° C. / min. By "non-overlapping" we mean that the onset temperature of the melting peak during heating is higher than the onset temperature of the recrystallization peak during cooling.
[0011] A third aspect of the invention is a method of forming a polyketone powder useful for producing an additive manufactured article, comprising the steps of: (i) reacting carbon monoxide with an alkene monomer in the presence of a Group 8 to Group 10 transition metal catalyst to form a feed polyketone powder; (ii) recovering the raw polyketone powder; (iii) Separating the powder to obtain a particle size distribution with a D of up to 300 micrometers. 90 forming a polyketone powder having a particle size and an average particle size of equivalent spherical diameter between 1 micrometer and 150 micrometers and an oversized polyketone powder; The method of the third aspect is useful for preparing the composition of the first aspect of the invention. The oversized polyketone powder can be further processed by milling to achieve the desired particle size and further processed to increase the crystallinity of the powder, for example to achieve the composition of the second aspect. The raw powder can also be further processed, such as by heating and extrusion, to form pellets which are further crystallized and crushed to achieve the composition of the second aspect.
[0012] A fourth aspect of the invention is a method of forming an article comprising heating a composition of the first or second aspect to a temperature sufficient to melt and combine the polyketone powder of the composition to form the article. The method is particularly useful for forming articles by additive manufacturing methods such as floating powder bed processes (e.g., SLS, HHS and MJF processes).
[0013] A fifth aspect of the invention is an article comprising fused particles of the compositions of the first and second aspects, desirably an article of intra- and inter-layer fused particles, such as those formed during layer-by-layer manufacturing.
[0014] The compositions can be fabricated into laminate manufactured articles taking advantage of the engineering plastic properties (e.g., heat and chemical resistance) for applications such as biocompatibility (medical), electrical, transportation (e.g., automotive, rail, trucking), plumbing, aerospace, food contact, industrial (e.g., machinery), and consumer (e.g., appliance) applications. [Brief description of the drawings]
[0015] [Figure 1] Plot of particle size distribution of polyketone powder of the composition of the present invention [Diagram 2] Optical micrograph of polyketone powder of the composition of the present invention [Diagram 3] Differential Scanning Calorimetry Plots of Polyketone Powders of the Composition of the Invention [Figure 4] Plot of particle size distribution of polyketone powder of the composition of the present invention [Diagram 5] Optical micrograph of polyketone powder of the composition of the present invention [Figure 6] Differential Scanning Calorimetry Plots of Polyketone Powders of the Composition of the Invention [Figure 7] Plot of particle size distribution of polyketone powder of the composition of the present invention [Figure 8] Optical micrograph of polyketone powder of the composition of the present invention [Figure 9] Differential Scanning Calorimetry Plots of Polyketone Powders of the Composition of the Invention [Figure 10] Differential Scanning Calorimetry Plots of Polyketone Powders of the Composition of the Invention [Figure 11] Differential Scanning Calorimetry Plots of Polyketone Powders of the Composition of the Invention DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The explanations and examples presented herein are intended to acquaint those skilled in the art with the invention, its principles, and its practical application. The particular embodiments of the present disclosure described are not intended to be exhaustive or to limit the scope of the invention.
[0017] As used herein, "one or more" means that at least one, or more, of the listed components may be used as disclosed. It will be understood that the functionality of any ingredient or component may be an average functionality due to imperfections in raw materials, incomplete conversion of reactants, and the formation of by-products.
[0018] It has been found that polyketone powder compositions useful in floating powder bed layered manufacturing processes can be formed by the reaction of carbon monoxide with alkene monomers in the presence of a Group 8 to Group 10 transition metal catalyst. Specifically, the process can be any one of those described in U.S. Pat. Nos. 4,894,435, 4,894,435, 5,138,032, and 5,138,032, each of which is incorporated herein by reference in its entirety. Specifically, the process, reaction conditions, and monomers are those described in U.S. Pat. No. 5,138,032, column 2, line 52 to column 5, line 17, which are specifically incorporated herein by reference. Examples of such catalysts include cobalt, nickel, and palladium.
[0019] Desirably, the alkene monomer comprises an olefin having from 2 to 12, 8 or 6 carbons. Illustratively, the alkene monomer is ethylene, or the alkene monomer comprises ethylene and at least one other olefin monomer, such as propylene. When the polyketone is a copolymer of ethylene and another olefin monomer, such as propylene, the amount of ethylene and the other olefin may be as described in U.S. Pat. No. 5,138,032, column 2, line 17 to column 3, line 14.
[0020] The composition of the first embodiment consists of a semi-crystalline polyketone powder having a bimodal melting peak as determined by an initial differential scanning calorimetry (DSC) scan at 20° C. / min. As described above, the semi-crystalline polyketone powder can be formed by recovering the powder directly from the reactor, subjecting it to any purification method known in the art (e.g., washing) and such as those described in the literature cited above, and then isolating the powder to achieve the desired powder size and size distribution.
[0021] Classification or separation of the raw polyketone powder particles from the reactor may be performed by any suitable method, such as those known in the art, to form polyketone with its desired particle size and morphology. By way of illustration, the raw particles may be sieved to remove any oversized or undersized particles and alter the size distribution accordingly. Other sizing methods, such as centrifugation, settling and air cyclones, may also be utilized.
[0022] Surprisingly, the crystallization or recrystallization peaks (used interchangeably here) overlap with the melting peaks in the initial DCS scans of the polyketone powders and still produce powders with good properties, no warping or distortion, and that can be additively manufactured.
[0023] The crystallization temperature (Tc) of polyketone powders is lower than the melting temperature (Tm) of semicrystalline polymers, which is determined by the melting peak and the crystallization peak, and in the case of a bimodal peak, by the lower temperature peak. Generally, the Tc of polyketones is about 10° C. to 40 or 50° C. lower than the Tm. Tm and Tc are determined from the DSC melting peak as described in ASTM D3418, using the midpoint of the melting peak. The onset of the Tm and Tc peaks are determined as per ASTM D3418 (i.e., deviation of the scan from linearity).
[0024] Directly produced polyketone powders may have a morphology that allows for layer-by-layer manufacturing without the need for flow aids. Desirably, polyketones with such desirable flow properties have particle shape, particularly particle roundness, which aids in flowability and may be expressed in terms of circularity, or circularity, derived from microscopic images of individual particles, where the circularity of an individual particle is determined by the formula: 4πA / P 2 where A is the area of the particle and P is the perimeter of the particle, both viewed from a random perspective. A related parameter, sphericity, is derived as the square root of the circularity. Circularity is a number greater than zero and less than or equal to 1. A perfectly circular particle is said to have a circularity of 1.00. Tables of population circularity data are presented in such a way that various levels of circularity (e.g., 0.65, 0.75, 0.85, 0.90, and 0.95) are accompanied by the percentage of the particle sample population that has a circularity greater than the tabulated value. Circularity is determined at a solidity filter level of 0.9 or 0.95. Solidity filters are filters used to remove overlapping particles in two-dimensional micrographs that are available in commercially available image analysis software. Solidity is essentially the area of the particle (particle area) that lies on the area of the region defined by the major and minor axes of the particle area in a two-dimensional micrograph. The size and shape of the particles can be measured by any suitable method known in the art for measuring particle size by diameter. In some embodiments, the size and shape of the particles are determined by laser diffraction as known in the art. For example, the particle size can be determined using a laser diffractometer such as a Microtrac S3500 equipped with a static image analysis accessory using PartAnSI software to analyze captured images of the particles. It is desirable that at least about 65%, 70%, 80%, 95% or 99% (by number) of the particles have a circularity of at least about 0.8, 0.85, 0.9 or 0.95 for the powder separated from the reactor and classified without further processing other than purification.
[0025] Similarly, polyketone powders separated and classified directly from the reactor, without the addition of any flow aids, generally have a flowability of at least about 0.5 g / sec, 1 g / sec, or 2 g / sec, or any practically achievable rate (e.g., 50 g / sec) using a 15 mm nozzle, as determined by Method A of ASTM D1895.
[0026] In another embodiment of the polyketone powder of the present invention, the oversized polyketone powder from the reactor may be subjected to a size reduction process, which may be further separated and classified if desired. The grinding may be performed by any suitable method, such as those known in the art. By way of example, milling at a temperature at which the semi-crystalline polyketone becomes brittle may be used, which is commonly referred to as freeze milling. Generally, freeze milling temperatures may range from about below 0° C., below −25° C., below −50° C., to about −75° C., −100° C., −150° C., or −190° C. In one embodiment, cooling is performed by dry ice or liquid nitrogen. These powders will have reduced flowability and circularity due to the grinding process, but may nevertheless be used to form the desired layered manufacturing article when used with processing aids known in the art, such as flow aids.
[0027] Another example of the polyketone powder of the present invention is one in which the polyketone powder from the reactor is heated and molded in an extruder to form pellets. The pellets can then be ground and subjected to any desired separation and classification as described in the previous paragraph. Due to the subsequent thermal history after formation in the reactor, these powders tend to have a unimodal Tm, with little or no overlap between the melting peak and the crystallization peak. Similarly, because these powders have been ground, they tend to have a morphology similar to that described for the oversized reactor powder.
[0028] The semi-crystalline polyketones of the present invention have a crystallinity of at least about 15% by weight to substantially crystalline, with higher degrees of crystallinity being more desirable. Desirably, the crystallinity is anywhere from 20%, 25% or 30% to substantially crystalline, 90%, 80%, 75%, 60% or 55%. The crystallinity may be determined by any suitable method, such as those known in the art. Illustratively, the percent crystallinity may be determined by X-ray diffraction, including wide-angle X-ray diffraction (WAXD), for example, using a Rigaku SmartLab X-ray diffractometer, or by differential scanning calorimetry (DSC), for example, using a TA Instruments DSC250 differential scanning calorimeter ASTM D3418-15.
[0029] In another example, any of the polyketone powders described above can be treated to increase the crystallinity of the polyketone powder. Such treatments may include any suitable treatment including dissolving and precipitating the polymer, or heating to a temperature below the temperature at which the polyketone sinters or melts (generally below and within about 20° C. of the onset of the melting peak). The atmosphere may be any atmosphere useful for preventing degradation of the polyketone, but may be air, dry air, or an inert gas (e.g., nitrogen or a noble gas). Examples of such methods are described in co-pending U.S. Provisional Patent Applications 63 / 208243 and 63 / 147822.
[0030] Further, crystallized polyketone powders may exhibit DSC scans in which the melting and crystallization peaks do not overlap. The interval between the onset temperatures of the melting and crystallization peaks may be 5, 10, or even 20 to 50° C. Treatment to increase crystallinity may preserve or improve the powder morphology similar to that described for polyketone powders classified directly from the reactor as described above. For example, heat treatment to increase crystallinity may result in particles having smoother surfaces and concomitant increased circularity as described above, which may result in powders with sufficient flowability for floating bed lamination manufacturing processes without flow aids.
[0031] The polyketone may have any DSC melting peak enthalpy useful for producing powders useful for additive manufacturing such as SLS. Typically, the enthalpy is at least 3 Joules / gram, but desirably at least 5, 10, 20, 30, 40 or 50 Joules / gram or more, up to any practical amount such as 200 Joules / gram. The enthalpy of the DSC melting peak may be determined according to the manner described in ASTM D3418.
[0032] The polyketone of the composition is
[0033] [ka]
[0034] where A is the residue of an alkene monomer which is converted to a saturated hydrocarbon group, m is from about 1 to 6, and n is from at least about 2 to any practical amount to achieve the desired number average molecular weight useful in the present invention. Exemplary useful number average molecular weights can be those which provide a melting temperature of from about 175° C. or 210° C. to about 270° C. or 300° C., and can be from about 1000 to 250,000 or from about 10,000 to 200,000 g / mole.
[0035] Desirably, the polyketone of the composition is a terpolymer of carbon monoxide, ethylene and another alkene monomer, such as an olefin of 3 to 12, 8 or 6 carbons, especially propylene. Such polyketones have random repeating units:
[0036] [ka]
[0037] where G is a saturated residue of an olefin of 3 to 12, 8 or 6 carbons polymerized with a double bond, and x / y is at least 2 to 100 or 50 or 20. Desirably, G is propylene. Illustratively, it may be desirable to have a ratio of ethylene to other alkenes of 2 to 100 by weight. The polyketone may be terminated with any useful group, such as alkyl groups, hydroxyls, esters, carboxylic acids, ethers or combinations thereof. Particular end groups may be generated by using solvents such as low molecular weight alcohols, such as methanol, or water or combinations thereof.
[0038] The semi-crystalline polyketone particles described above generally have particle sizes and size distributions that are useful for producing laminated manufacturing articles, typically having a mean or median particle size (D) of about 1 micrometer (μm), 10 μm, 20 μm, 30 μm, or 40 μm, to 150 μm, 125 μm, 110 μm, or 100 μm, by volume. 50 Similarly, semi-crystalline polyketones have D of up to 300 μm, 200 μm or 150 μm to allow for consistent heating and melting of the powder. 90 To aid in flowability, the polyketone preferably has a D by volume of at least 0.1 μm, 0.5 μm or 1 μm. 10 It is desirable to have D 90 means the particle size (equivalent spherical diameter) in the particle size distribution in which 90% by volume of the particles are equal to or smaller than that size, and similarly, D 50 means the particle size (equivalent spherical diameter) in a particle size distribution below which at least 50% by volume of the particles are smaller, and D 10 means the particle size (equivalent spherical diameter) in a particle size distribution below which at least 10% by volume of the particles are. Particle size may be determined by any suitable method, such as those known in the art, including, for example, laser diffraction of a sufficient number of particles (about 100 to about 200 particles) or image analysis of photomicrographs. Exemplary laser diffractometers are those manufactured by Microtrac, such as the Microtrac S3500.
[0039] The composition of the present invention may further comprise useful additives, such as those known in the art for producing articles, such as laminated manufacturing articles. The composition may also comprise additional thermoplastic polymer powders useful for laminated manufacturing, such as polyamides (e.g., nylon 6; nylon 6,6; nylon 4,6; nylon 6,9; nylon 5,10; nylon 6,10; nylon 11; nylon 6,12 and nylon 12). For example, the composition may have one or more of ultraviolet (UV) stabilizers, fillers, lubricants, plasticizers, pigments, flow aids, flame retardants, or solvents. It is desirable for the composition to be substantially free of solvents (i.e., up to 10 parts per million (ppm) by weight of the composition, up to 1 ppm, up to trace amounts). The amount of any particular additive may be any useful amount to achieve a particular property or characteristic for printing of an article formed therefrom. Generally, the amount of additive, if present, is up to about 50%, 25%, 10% or 5% by volume of the composition. The flow aid may be any compound known to improve the flow properties of powders, an example of which is fumed silica (eg, Aerosil 200).
[0040] The filler may be any useful filler, such as those known in the art. Examples of fillers include ceramic, metal, carbon (e.g., graphite, carbon black, graphene), polymeric particulates that do not melt or decompose at printing temperatures (e.g., crosslinked polymeric particulates, vulcanized rubber particulates, etc.), plant-based fillers (e.g., wood, nut shell, grain and rice husk powder or particles). Exemplary fillers include calcium carbonate, talc, silica, wollastonite, clay, calcium sulfate, mica, inorganic glass (e.g., silica, aluminosilicate, borosilicate, alkali aluminosilicate, etc.), oxides (e.g., alumina, zirconia, magnesia, silica "quartz", and calcia), carbides (e.g., boron carbide and silicon carbide), nitrides (e.g., silicon nitride, aluminum nitride), oxynitrides, combinations of oxycarbides, or combinations thereof. In certain embodiments, the filler comprises an acicular filler such as talc, clay minerals, inorganic glass filaments, metal filaments, or carbon filaments, mullite, mica, wollastonite, or combinations thereof. In particular embodiments, the filler comprises talc.
[0041] It has been found that the polyketone of the composition of the present invention can form shaped articles that do not deform or have undesirable amounts of residual stress. For example, but not limited to, the composition of the present invention can be manufactured into objects by additive manufacturing methods such as SLS, MJF, HSS or electrophotography. By way of illustration, in SLS, a layer of the composition of the present invention can be deposited on a bed at a fixed temperature below the melting temperature of the polyketone powder, and predetermined (selected) areas of the bed are sintered (fused) together using a heat source that is laser controlled and directed as described above. Multiple layers are then deposited in succession and sintered within and to previous layers to build an additively manufactured part.
[0042] Surprisingly, the polyketone powders of the composition, even when they exhibit melting and crystallization peak overlap without deformation, tend to fuse together or have undesirable amounts of residual stress within, and especially between, the layers of the additively manufactured part. The reason this behavior is observed is not understood, but without limitation, may be due to the presence of a bimodal melting peak in some cases. Typically, the "working range" for additively manufacturing semi-crystalline thermoplastic polymers is the temperature difference between the temperature at which the material begins to melt and the temperature at which it begins to recrystallize ("Tc"), which should be as large as possible. From the above, further crystallized polyketones may be further optimized such that the working range is anywhere from 10°C, 15°C, or 20°C to 60°C, 50°C, 30°C, or 25°C.
[0043] Since the polyketone powders of the compositions of the present invention exhibit good three-dimensional printability even when the melting and crystallization peaks overlap, they may be recycled and reused without further processing after being printed in a powder additive manufacturing process that includes heating and maintaining a bed of powder at a temperature just below the starting melting temperature of the polyketone. If desired, the recycled powder may be mixed with any of the polyketone powders described herein that have not yet been additively manufactured to achieve the desired printability or part properties. The proportion of recycled polyketone that constitutes the compositions of the present invention may be any amount from substantially all, 90%, 75%, 50%, 40% or 30% by weight of the composition to about 1%, 5% or 10% by weight. The thermal properties of the recycled powder are generally as described above for the granulated and ground polyketones for the polyketone powders of the present invention. The morphology and size distribution are similarly as described herein, with the morphology most similar to that of the particular initial polyketone powder used to form the additively manufactured article.
[0044] The compositions of the present invention may be used to produce layered manufactured articles comprised of a plurality of fused polyketones of the present invention. In particular, the compositions may be used to produce layered manufactured articles produced by sequential selective heating of powder layers to fuse particles within and between layers, such as SLS, HSS and MJF. EXAMPLES
[0045] Example 1: The polyketone powder is produced in the course of the procedure described in US Patent No. 5,138,032, column 2, line 52 to column 5, line 17. The powder obtained directly from the reactor is sieved through a sieve with 150 micrometer openings to form polyketone powder and oversized polyketone powder (particles that do not pass through the sieve) having a particle size and volumetric particle size distribution as shown in Figure 1, measured using a Microtrac S3500 in water. 10 is about 82 micrometers, and D 50 is about 110 micrometers, and D 90 is about 152 micrometers. The shape and morphology of the powder is shown in the optical micrograph of Figure 2, where it is evident that the particles are highly uniform and substantially circular with an average circularity of greater than 0.9. The melting and crystallization peaks are shown in the DSC scan of Figure 3, where it is evident that the melting peak is bimodal and that the crystallization and melting peaks overlap.
[0046] The polyketone powders are printed using a Farsoon ST252P SLS printer. The printed parts (e.g., dog-bone specimens for mechanical testing) were printed without distortion and had good surface finish and properties as shown in Table 1.
[0047] [Table 1]
[0048] Example 2: The oversized polyketone powder is freeze-milled for a period of time to produce a polyketone powder having the particle size and particle size distribution, particle morphology, and thermal properties shown in Figures 4-6. 10 is about 57 micrometers, and D 50 is about 90 micrometers, and D 90 is about 170 micrometers. Again, it is very clear that the polyketone powder has a bimodal melting peak, with the crystallization peak and the bimodal melting peak overlapping. This powder is distortion-free, printed in the same manner as Example 1, and has good mechanical properties as shown in Table 2.
[0049] [Table 2]
[0050] Example 3: 70% recycled powder by weight from the printing of the sample of Example 1 is mixed with 30% polyketone powder by weight from Example 1 to form a 70% recycled polyketone powder. The particle size and size distribution, particle morphology and thermal properties are shown in Figures 7 to 9. This powder was printed in the same manner as Example 1, and the part had the properties as shown in Table 3 and showed no distortion. Although the bimodality of the melting peak is not evident from the figures, it may be that the thermal history of the 30% or recycled powder attributed to the powder of Example 1 results in a low temperature tail of the melting peak, which again overlaps with the crystallization peak. In other words, and without limitation, the overlap may be due to a short period of time above the melting temperature experienced during the printing process, or a holding temperature of the SLS powder bed below the melting temperature of the polyketone.
[0051] [Table 3]
[0052] Example 4: The raw polyketone powder from Example 1 is granulated in an extruder. The polyketone pellets are freeze milled and sieved as in Example 1. The thermal properties of the powder are shown in Figure 10. From the figure it is clear that the melting peak is substantially unimodal, yet overlaps with the crystallization peak.
[0053] Example 5: The polyketone pellets from Example 4 are further crystallized by heating in air at 185° C. for 4 hours. The thermal properties of the powder are shown in Figure 11. From the figure, it is evident that the melting peak is clearly distinct and there is no overlap between the melting peak and the crystallization peak, which are separated by about 15° C.
[0054] Preferred embodiments of the present invention will be described below in detail.
[0055] EMBODIMENT 1 An initial differential scanning calorimetry (DSC) scan at 20°C / min determined a bimodal melting peak and a D of up to 300 micrometers. 90 A composition comprising a semi-crystalline polyketone powder having a particle size and an average particle size equivalent spherical diameter of 1 micrometer to 150 micrometers.
[0056] EMBODIMENT 2 2. The composition of embodiment 1, wherein at least 90% by number of the particles of the semi-crystalline polyketone powder have a circularity of at least about 0.9.
[0057] EMBODIMENT 3 The polyketone is:
[0058] [ka]
[0059] wherein A is the residue of an alkene monomer which is converted to a saturated hydrocarbon group, m is from about 1 to 6, and n is at least about 2 to 10,000.
[0060] EMBODIMENT 4 The composition of any one of the preceding embodiments, wherein the semi-crystalline polyketone powder is a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer.
[0061] EMBODIMENT 5 The composition of embodiment 4, wherein the other alkene monomer is an olefin.
[0062] EMBODIMENT 6 The composition of embodiment 5, wherein the olefin is propylene.
[0063] EMBODIMENT 7 The composition of any one of embodiments 4 to 6, wherein the ethylene is present in a ratio of ethylene / other alkenes of about 2 to 100.
[0064] EMBODIMENT 8 8. The composition of any one of the preceding claims, wherein the polyketone is terminated with an alkyl group, a hydroxyl, an ester, a carboxylic acid, an ether, or a combination thereof.
[0065] EMBODIMENT 9 9. The composition of any one of the preceding claims, wherein the polyketone has a recrystallization peak that overlaps with a portion of the bimodal melting peak during initial heating and cooling DSC scans.
[0066] EMBODIMENT 10 10. The composition of any one of the preceding claims, wherein the polyketone has a unimodal melting peak upon subsequent DSC scanning.
[0067] EMBODIMENT 11 11. The composition of embodiment 10, wherein the subsequent DSC scan has a recrystallization peak that overlaps with a portion of the unimodal melting peak.
[0068] EMBODIMENT 12 12. The composition of any one of the preceding claims, wherein the polyketone has a crystallinity of at least about 15% by volume.
[0069] EMBODIMENT 13 13. The composition of any one of the preceding claims, wherein the powder has a flowability of at least about 0.5 g / sec as determined by ASTM D1895 using a 15 mm nozzle.
[0070] EMBODIMENT 14 14. The composition of any one of the preceding claims, wherein the composition further comprises one or more of a UV stabilizer, a filler, a lubricant, a plasticizer, a pigment, a flow aid, a flame retardant, other polymeric powders, or a solvent.
[0071] EMBODIMENT 15 15. The composition of any one of the preceding embodiments, wherein the composition is substantially free of solvent.
[0072] EMBODIMENT 16 The polyketone powder has (i) a D 90 (ii) a particle size D of at least 10 μm 10 and (iii) an average particle size of about 20 μm to about 50 μm.
[0073] EMBODIMENT 17 A composition comprising a semi-crystalline polyketone powder having non-overlapping melting and recrystallization peaks as determined by differential scanning calorimetry (DSC) scanned at heating and cooling rates of 20°C / min.
[0074] EMBODIMENT 18 18. The composition of embodiment 17, wherein the melting peak and the recrystallization peak have melting peak onset temperatures and recrystallization onset temperatures, respectively, that are at least 10° C. apart from one another.
[0075] EMBODIMENT 19 The polyketone is:
[0076]
change
[0077] wherein A is the residue of an alkene monomer which is converted to a saturated hydrocarbon group, m is from about 1 to 6, and n is at least about 2 to 10,000.
[0078] EMBODIMENT 20 20. The composition of any one of embodiments 17 to 19, wherein the semicrystalline polyketone powder is a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer.
[0079] EMBODIMENT 21 The composition of embodiment 20, wherein the other alkene monomer is an olefin.
[0080] EMBODIMENT 22 22. The composition of embodiment 21, wherein the other alkene monomer is propylene.
[0081] EMBODIMENT 23 23. The composition of any one of embodiments 20 to 22, wherein the ethylene is present in a ratio of ethylene to other alkenes of from about 2 to 100 by weight.
[0082] EMBODIMENT 24 24. The composition of any one of embodiments 20 to 23, wherein the polyketone is terminated with an alkyl group, a hydroxyl, an ester, a carboxylic acid, an ether, or a combination thereof.
[0083] EMBODIMENT 25 25. The composition of any one of embodiments 17 to 24, wherein the polyketone has a crystallinity of at least about 15% by volume.
[0084] EMBODIMENT 26 26. The composition of any one of embodiments 17 to 25, wherein the powder has a flowability of at least about 0.5 g / sec as determined by ASTM D1895 using a 15 mm nozzle.
[0085] EMBODIMENT 27 27. The composition of any one of embodiments 17 to 26, wherein the composition further comprises one or more of a UV stabilizer, a filler, a lubricant, a plasticizer, a pigment, a flow aid, a flame retardant, or a solvent.
[0086] EMBODIMENT 28 28. The composition of any one of embodiments 17 to 27, wherein the composition is substantially free of solvent.
[0087] EMBODIMENT 29 The polyketone powder has (i) a D 90 (ii) a particle size D of at least 10 μm 10 and (iii) an average particle size of about 20 μm to about 50 μm.
[0088] EMBODIMENT 30 30. The composition of any one of the preceding claims, wherein the polyketone powder has a detectable amount of a Group 8 to Group 10 transition metal catalyst.
[0089] EMBODIMENT 31 31. The composition of embodiment 30, wherein the Group 8 to 10 transition metal catalyst is nickel, cobalt, palladium, or a combination thereof.
[0090] EMBODIMENT 32 1. A method of forming a polyketone powder useful for producing laminated manufactured articles, comprising: (iv) reacting carbon monoxide with alkene monomers in the presence of a Group 8 to Group 10 transition metal catalyst to form a feed polyketone powder; (ii) recovering the raw polyketone powder; (iii) isolating the raw polyketone powder to obtain a polyketone powder having a D 90 forming a polyketone powder having a particle size and an average particle size of equivalent spherical diameter between 1 micrometer and 150 micrometers and an oversized polyketone powder; The method comprising:
[0091] EMBODIMENT 33 33. The method of embodiment 32, wherein at least about 90% of the particles have a circularity of at least about 0.9.
[0092] EMBODIMENT 34 33. The method of embodiment 32, further comprising crushing the oversized polyketone powder to form a crushed polyketone powder.
[0093] EMBODIMENT 35 35. The method of embodiment 34, wherein at least 90% by number of the crushed polyketone powders have a circularity of at least about 0.8.
[0094] EMBODIMENT 36 The crushed polyketone powder has a D 90 36. The method of embodiment 35, wherein the particle size and average particle size of equivalent spherical diameter is from 1 micrometer to 100 micrometers.
[0095] EMBODIMENT 37 37. The method of any one of claims 32 to 36, wherein the polyketone powder, the raw polyketone powder, or the crushed polyketone powder is subjected to conditions to further crystallize the polyketone powder.
[0096] EMBODIMENT 38 38. The method of embodiment 37, wherein the further crystallizing step comprises heat treating any one of the polyketone powders to a temperature 50° C. below its peak melting temperature as determined by DSC for a time to increase crystallinity to form a polyketone having increased crystallinity.
[0097] EMBODIMENT 39 39. The method of embodiment 38, wherein the polyketone with increased crystallinity has a peak melting onset temperature and a recrystallization onset temperature that are at least 10° C. apart.
[0098] EMBODIMENT 40 33. The method of embodiment 32, wherein the recovered raw polyketone powder is heated and formed into pellets, and the pellets are then crystallized, milled and classified to form a further crystallized polyketone powder.
[0099] EMBODIMENT 41 32. A method of forming an article, comprising heating the composition of any one of embodiments 1 to 31 to a temperature sufficient to melt and bond the polyketone powder of the composition to form the article.
[0100] EMBODIMENT 42 42. The method of embodiment 41, wherein the method is an additive manufacturing method.
[0101] EMBODIMENT 43 43. The method of embodiment 42, wherein the layer-by-layer manufacturing process comprises selective fusion by direct melting of polyketone powders of the composition.
[0102] EMBODIMENT 44 44. The method of any one of embodiments 41 to 43, wherein the composition consists of recycled polyketone powder.
[0103] EMBODIMENT 45 45. The method of embodiment 44, wherein the recycled polyketone powder is present in an amount of about 10% to 50% by weight of the polyketone powder present in the composition.
[0104] EMBODIMENT 46 46. An article comprising an article formed by the method of any one of embodiments 41 to 45.
[0105] EMBODIMENT 47 Melting and crystallization peaks as determined by an initial differential scanning calorimetry (DSC) scan at 20°C / min and a D of up to 300 micrometers 90 1. A composition comprising a semi-crystalline polyketone powder having a particle size and an average particle size of an equivalent spherical diameter from 1 micrometer to 150 micrometers, wherein the melting peak and the crystallization peak overlap.
[0106] EMBODIMENT 48 The composition of embodiment 17 or 47, wherein the melting peak is unimodal.
[0107] EMBODIMENT 49 32. The composition of any one of the preceding claims, wherein the melting peak has a melting enthalpy of the polyketone powder of at least 5 Joules / gram.
[0108] EMBODIMENT 50 50. The composition of embodiment 49, wherein the polyketone powder has a melting enthalpy of at least 20 Joules / gram.
Claims
1. A bimodal melting peak as determined by an initial differential scanning calorimetry (DSC) scan at 20° C. / min and a D peak of up to 300 micrometers. 90 1. A composition comprising an aliphatic semi-crystalline polyketone powder having a particle size and an average particle size of equivalent spherical diameter from 1 micrometer to 150 micrometers, the aliphatic semi-crystalline polyketone powder being a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer.
2. 2. The composition of claim 1, wherein said other alkene monomer is an olefin having from 3 to 12 carbons and said ethylene is present in a ratio of 2% to 100% by weight of ethylene / other alkene.
3. The composition of claim 2 wherein the olefin is propylene.
4. 2. The composition of claim 1, wherein the polyketone has a recrystallization peak that overlaps with a portion of the bimodal melting peak during initial heating and cooling DSC scans.
5. 10. The composition of claim 1, wherein the polyketone has a unimodal melting peak upon subsequent DSC scanning.
6. 6. The composition of claim 5, wherein the subsequent DSC scan has a recrystallization peak that overlaps with a portion of the unimodal melting peak.
7. 1. A composition comprising an aliphatic semi-crystalline polyketone powder having non-overlapping melting and recrystallization peaks as determined by differential scanning calorimetry (DSC) scanned at heating and cooling rates of 20° C. / min, the aliphatic semi-crystalline polyketone powder being a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer, the aliphatic semi-crystalline polyketone powder having a D 90 particle size of up to 300 micrometers and an average particle size of equivalent spherical diameter of 1 micrometer to 150 micrometers.
8. 8. The composition of claim 7, wherein said melting peak and said recrystallization peak have melting peak onset temperatures and recrystallization onset temperatures, respectively, that are at least 10 degrees Celsius apart from one another.
9. 8. The composition of claim 7, wherein the semi-crystalline polyketone powder is a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer which is an olefin having from 3 to 12 carbons, and the ethylene is present in a ratio of 2% to 100% by weight of ethylene / other alkene.
10. The composition of claim 9 wherein said other alkene monomer is propylene.
11. 1. A method of forming an aliphatic polyketone powder useful for producing laminated manufactured articles, comprising: (i) reacting carbon monoxide with an alkene monomer in the presence of a Group 8 to Group 10 transition metal catalyst to form a feed polyketone powder; (ii) recovering the raw polyketone powder; (iii) isolating the raw polyketone powder to obtain polyketone particles having a D of up to 300 micrometers. 90 forming a polyketone powder having a particle size and average particle size of 1 micrometer to 150 micrometers equivalent spherical diameter and greater than 300 micrometers, said polyketone powder being a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer; The method comprising:
12. 12. The method of claim 11, wherein the polyketone powder, the raw polyketone powder, or the crushed polyketone powder are subjected to conditions to further crystallize the polyketone powder, the further crystallizing step comprising heat treating any one of the polyketone powders to a temperature 50°C below its peak melting temperature as determined by DSC for a time to increase crystallinity to form a polyketone having increased crystallinity.
13. 13. The method of claim 12, wherein the polyketone with increased crystallinity has a peak melting onset temperature and a recrystallization onset temperature that are at least 10°C apart.
14. 13. The method of claim 12, wherein the polyketone powder comprises recycled polyketone powder present in an amount of 10% to 50% by weight of the polyketone powder.
15. Melting and crystallization peaks as determined by an initial differential scanning calorimetry (DSC) scan at 20° C. / min and a D of up to 300 micrometers 90 1. A composition comprising an aliphatic semi-crystalline polyketone powder having a particle size and an average particle size of 1 micrometer to 150 micrometers equivalent spherical diameter, wherein the melting peak and the crystallization peak overlap, and wherein the composition comprising the aliphatic semi-crystalline polyketone powder is a copolymer of ethylene, carbon monoxide, and at least one other alkene monomer.
16. 16. The composition of claim 15, wherein the melting peak is unimodal.
17. 17. The composition of any one of claims 1 to 10, 15, and 16, wherein the melting peak has a melting enthalpy of the polyketone powder of at least 5 Joules / gram.
18. 17. The composition of any one of claims 1 to 10, 15 and 16, wherein the polyketone powder has a detectable amount of a Group 8 to Group 10 transition metal catalyst.
19. The polyketone powder has (i) a D 90 (ii) a particle size of at least 10 μm, 10 and (iii) an average particle size of from 20 μm to 50 μm.
20. 17. A method of forming an article, comprising heating the composition of any one of claims 1 to 10, 15, and 16 to a temperature sufficient to melt and bond the polyketone powder of the composition to form the article by an additive manufacturing process.
Citation Information
Patent Citations
Polyaryletherketone powder and preparation method thereof
CN110655666A
Aliphatic polyketone resin composition
JP1999302530A
Catalyst composition for olefin polymerization and method of polymerization using the same
JP2003128721A
PAEK fine powder, and method for layer-wise generation of three-dimensional object
JP2013064153A
Polyketon drying system of mesh screen
KR1020160108820A